Microbial community evolution and functional trade-offs of biofilm in odor treatment biofilters. (15th May 2023) - Wang, Yong-Chao; Lv, Ya-Hui; Wang, Can; Jiang, Guan-Yu; Han, Meng-Fei; Deng, Ji-Guang; Hsi, Hsing-Cheng
Highlights: Three distinct developmental phases during biofilter operation were observed. Trade-offs in biofilm community and function was studied at different phases. QS related genera active a fast biofilm accumulation at startup phase. Odorants degradation dominated biofilm community evolution at stable operation phase. QQ behaviors and competition between species play important role in clogging phase. Abstract: Biofilters inoculated with activated sludge are widely used for odor control in WWTP. In this process, biofilm community evolution plays an important role in the function of reactor and is closely related to reactor performance. However, the trade-offs in biofilm community and bioreactor function during the operation are still unclear. Herein, an artificially constructed biofilter for odorous gas treatment was operated for 105 days to study the trade-offs in the biofilm community and function. Biofilm colonization was found to drive community evolution during the start-up phase (phase 1, days 0–25). Although the removal efficiency of the biofilter was unsatisfactory at this phase, the microbial genera related to quorum sensing and extracellular polymeric substance secretion led to the rapid accumulation of the biofilm (2.3 kg biomass/m 3 filter bed /day). During the stable operation phase (phase 2, days 26–80), genera related to target-pollutant degradation showed increases in relative abundance, which accompanied a high removal efficiency and a stable accumulation of biofilm (1.1 kg biomass/m 3 filter bed/day). At the clogging phase (phase 3, days 81–105), a sharp decline in the biofilm accumulation rate (0.5 kg biomass/m 3 filter bed /day) and fluctuating removal efficiency were observed. The quorum quenching-related genera and quenching genes of signal molecules increased, and competition for resources among species drove the evolution of the community in this phase. The results of this study highlight the trade-offs in biofilm community and functions during the operation of bioreactors, which could help improve bioreactor performance from a biofilm community perspective. Graphical abstract: Image, graphical abstract